2019
DOI: 10.15548/jt.v26i2.521
|View full text |Cite
|
Sign up to set email alerts
|

Translating from English into Indonesian: Which techniques to teach EFL students to be professional translators?

Abstract: The credits for translation courses offered at the study program of English Language Teaching at a university level in Indonesia are very limited, which is not sufficient to teach and facilitate practices for all techniques of translation. Therefore, the students should only be taught techniques frequently used in translation from English to Indonesian. This research was to analyze translation techniques commonly used in translating from English to Indonesian. The data were collected from Colors magazine, an i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
3
0
Order By: Relevance
“…Some of the methods proposed were literal translation, replacement, and free translation (Triyono, 2019). Regarding the technique or method in a translation process, research conducted by Mustafa & Kholid (2019) showed that there were some of the most dominant techniques used by a translator in translating English (source language) into Indonesian (target language) to achieve equivalence or naturalness of the translation works. These techniques were amplification, reduction, transposition, borrowing, modulation, and literal translation.…”
Section: Discussionmentioning
confidence: 99%
“…Some of the methods proposed were literal translation, replacement, and free translation (Triyono, 2019). Regarding the technique or method in a translation process, research conducted by Mustafa & Kholid (2019) showed that there were some of the most dominant techniques used by a translator in translating English (source language) into Indonesian (target language) to achieve equivalence or naturalness of the translation works. These techniques were amplification, reduction, transposition, borrowing, modulation, and literal translation.…”
Section: Discussionmentioning
confidence: 99%
“…Omission is frequently found in translated versions into Indonesian to achieve naturalness. In translating magazine articles, omission is used avoid redundant information because it has been implied in previous sentences or phrases (Mustafa & Kholid, 2019). However, this translation technique was infrequently used in translating the smartphone user manual.…”
Section: Discussionmentioning
confidence: 99%
“…There have been many studies on the translation techniques used in translating texts from English into Indonesian, such as translation of magazine articles (Mustafa & Kholid, 2019), novels (Aziz, 2015), web pages (Kamil, 2014), and tourism news texts (Ariyaningsih & Santika, 2018). However, translation of a technology manual book is underresearched.…”
Section: Introductionmentioning
confidence: 99%